EFFECTIVE WAYS TO FOSTER LOGICAL THINKING ABILITIES OF STUDENTS IN MATH CLASSES (Intent Research Scientific Journal, 2023)
Current article highlights the effective teaching strategies for fostering logical thinking abilities of students in math classes.